Semiochemistry of the Bruchidae species. (June 2018) - Rodríguez, Sergio A.
Abstract: The coleopteran insects of the Bruchidae family are one of the major pests of stored products like beans and leguminous seeds in general. Bruchids have co-evolved with the seeds of leguminous plants dealing with the toxic compounds from the seeds. These insects eat a considerable part of the stored product and also contaminate the grains with their dead bodies, wings, and excreta. Among all the pests, insect damage in stored grains alone could escalate to cause up to 100% loss. An alternative to managing this pest insect is the use of pheromones. Sex pheromones provide important signals in sexual communication. Generally, volatile sex pheromones are released to attract the opposite sex from a distance, and contact sex pheromones help in partner discrimination and can elicit courtship. The main focus of this article is to review the results on the chemical identification of pheromones of insect pests of the family Bruchidae in stored products. Highlights: The results on the chemical identification of pheromones of the family Bruchidae were reviewed. Biological activities of compounds were discussed. An Integrated Pest Management point of view is given.